Letter (copy) : Relief for Spain - Tewson, Vincent
030-0076-001 Secretary's. HVT/FC. The Opera House, Winter Gardens, Blackpool. 7th September, 1938. His Excellency The Spanish Ambassador, Spanish Embassy, LONDON. Your Excellency, RELIEF FOR SPAIN. I desire to thank you for your letter of the 2nd instant which has been forwarded from our London office to Blackpool where we are holding our Annual Congress. I have this morning seen Mr. Daniel Fernandez-Shaw who has fully explained the position and regard will be paid to the proposals which are now made in connection with co-ordinating relief work in Spain. Our Congress will this week be discussing the question of intensifying our relief work and we hope that as a result we shall be able to continue with the work of the International Solidarity Fund. Yours faithfully, Assistant Secretary. 292/946/30/76